Effects of the metal electrode on dielectric constant of MgO nanoparticles - (:unkn) unknown (My University, 2010)
In this study, effects of the metal electrode on dielectric properties of MgO nanoparticles were investigated. MgCl2.6H2O were dissolved in ethanol and aged for a long time under stirring. The particles were obtained by precipitation method. Crystal structure of particles was investigated using X-ray diffraction. In order to determine the electrical properties of the MgO nanoparticles, metal electrodes were deposited onto both sides of the MgO pellets using thermal evaporation method in high vacuum (<10-6 mbar). Dc and ac electrical properties of two MgO pellets with different metal electrodes (Au and Ag) were determined under vacuum ambient as a function of temperature (293-523 K). ac electrical measurements were carried out between the frequencies 40 Hz-105 Hz. Activation energy values of the MgO pellets with different metal electrodes were calculated using the relation σdc= σoe-Ea/kt and from slope of the dc conductivity (σdc) - inverse of temperature (1/T) curve. Dielectric constant was calculated as a function of both frequency and temperature. MgO pellet with Au electrode showed a small decrease with increasing frequency in the measured frequency range. © 2009 American Institute of Physics.
Keywords: Dielectric; MgO; Nanoparticle; Sol-gel